Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Inkuiri Terbimbing Pada Materi Hidrolisis Garam Untuk Siswa SMA - Apriani, Ayu; Afgani, M. Win; Tri Astuti, Resti (LPPM Universitas Negeri Jakarta, 2021)
This research is a R & D (Research and Development) which aims to find out the validity and response of learning to LKPD based on guided inquiry chemistry on salt hydrolysis materials. The development procedures of this research adopt and ADDIE model carried out to stage three. This study included three validator, namely media / design expert validators, linguists, and material experts. The subjects of one-on-one and small-scale trials were students of SMA Muhammadiyah 1 Palembang. The data collection instruments used validation sheets, student response questionnaires, and interview guidelines. The results of this study indicate that the guided inquiry-based chemistry LKPD on salt hydrolysis material obtained a percentage of design / media experts of 96.42% with a very valid category, linguists obtained a percentage of 100% with a very valid category, and material experts obtained a percentage of 87 , 4% with very valid category. The average percentage value of the three validators is 93.70% with a very valid category. The response of students to the developed chemical LKPD can be categorized as very interesting, where on a one-on-one scale trial obtained a percentage value of 83,25% with a very attractive category, on a small-scale trial obtained a percentage value of 86.04% and stated very interesting. Key words: LKPD, guided inquiry, hydrolysis